Asymmetric Cost Behavior Across Life Cycle Stages - Abdelhay, Mohamed Abdelghany; Youssef, Ahmed Mahmoud; Awad, Mohamed Hamdy (International Journal of Accounting and Financial Reporting, 2021)
The traditional model of cost behavior has been criticized for its symmetric cost behavior assumption. A new model has been proposed assuming that costs respond differently to upward and downward activity changes. The main objectives of this paper are to investigate the existence, degree, and nature of asymmetric cost behavior (ACB) phenomenon and examine how the organization life cycle (OLC) affects this phenomenon in the context of Egypt. The current study achieves these objectives by employing multiple regression to explore the behavior of cost of goods sold (COGS), selling, general and administrative cost (SGA), and total cost (TC) for 1577 firm-year observations (99 manufacturing firms) during the period from 2000 to 2019. The results demonstrate that all three cost proxies (COGS, SGA, and TC) are sticky with the highest degree of stickiness to TC. In addition, OLC is a conditional factor that affects how costs behave in response to change in activity level. Consistent with theoretical propositions, both COGS and TC exhibit anti-stickiness behavior for firms in the introduction stage and stickiness behavior for firms in the growth, mature, and shakeout/decline stages. However, SGA is only sticky for firms in the mature stage. However, the hypotheses related to asymmetric behavior of SGA were rejected for firms in the introduction, growth, and shakeout/decline stages.